Gastric emptying performance of stomach-partitioning gastrojejunostomy versus conventional gastrojejunostomy for treating gastric outlet obstruction: A retrospective clinical and numerical simulation study - Zhang, Haiqiao; Xu, Fengyan; Zheng, Zhi; Liu, Xiaoye; Yin, Jie; Fan, Zhenmin; Zhang, Jun (Frontiers in Bioengineering and Biotechnology, 2023)
Purpose: This study evaluated the gastric emptying performance of stomach-partitioning gastrojejunostomy (SPGJ) versus conventional gastrojejunostomy (CGJ) for treating gastric outlet obstruction (GOO). Methods: First, 73 patients who underwent SPGJ (n = 48) or CGJ (n = 25) were involved. Surgical outcomes, postoperative recovery of gastrointestinal function, delayed gastric emptying, and nutritional status of both groups were compared. Second, a three-dimensional stomach model was constructed based on the gastric filling CT images from a GOO patient with a standard stature. The present study evaluated SPGJ numerically by comparing it with CGJ in terms of local flow parameters such as flow velocity, pressure, particle retention time, and particle retention velocity. Results: Clinical data found that SPGJ had significant advantages over CGJ in terms of time to pass gas (3 versus 4 days, P < 0.001), time to oral intake (3 versus 4 days, P = 0.001), postoperative hospitalization (7 versus 9 days, P < 0.001), the incidence of delay gastric emptying (DGE) (2.1% versus 36%, P < 0.001), DGE grading (P < 0.001), and complications (P < 0.001) for GOO patients. Moreover, numerical simulation revealed that the SPGJ model would induce contents in stomach discharge to the anastomosis at a higher speed, and only 5% of that flowed to the pylorus. SPGJ model also had a low-pressure drop as the flow from the lower esophagus to the jejunum, reducing the resistance to food discharge. Besides, the average retention time of particles in the CGJ model is 1.5 times longer than that in the SPGJ models, and the average instantaneous velocity in CGJ and SPGJ models are 22 mm/s and 29 mm/s, respectively. Conclusions: Compared with CGJ, patients after SPGJ had better gastric emptying performance and better postoperative clinical efficacy. Therefore, we think that SPGJ may be a better option for treating GOO.